Diksiminasi dan Ketidakadilan terhadap Perempuan Pribumi dalam Novel Lebih Putih Dariku - Aksal Juliana; Andalusia Permatasari (UNISBA Press, 2023)
Abstract. Women always experience discrimination and injustice in social life. Women have always been treated unfairly by the structure of society. Women always get discrimination that makes them the other for the dominant subject. In the novel More Putih Than Me, there are forms of discrimination and injustice against indigenous women during the Dutch East Indies period. For this reason, this research was conducted with the aim of seeing that there is discrimination and injustice against women contained in the novel Lagi Putih Dariku. The method used is a qualitative method with Sara Mills' critical discourse analysis approach. Sara Mills' Critical Discourse Analysis is used to see how women are represented in the text through the position of subject-object and writer-reader. The results of the study show that in the novel Putih Putih Dariku there is discrimination and injustice experienced by indigenous women. In the position of the subject, namely Isah as the narrator as well as the object being told, she experienced discrimination and injustice as a native woman during the Dutch East Indies period. In the reader's position, the reader is brought into the text by using the firstperson point of view